2012
DOI: 10.5923/j.microbiology.20120201.03
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Laccase Production in Pluerotus pulmonarius-LAU 09 by Mutation

Abstract: The strain improvement of P. pulmonarius LAU 09 for laccase production was carried out by UV-light exposure at 210nm (UV-sterilizer, Millipore xx63 70000) for 90minutes. The highest laccase activity of 2.5 Uml-1 was produced by LAU 90 (mutant) in comparison with obtained yield by wild type LAU 09 (1.75 Uml-1). The optimal physiological parameters for optimum laccase production by LAU 90 are 30OC of temperature, pH of 5.0 and incubation of 168hours. The mutant strain gave the highest total enzyme activity and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The increased yield in mannanase production in the mutants is a proof of true strain improvement. This was in agreement with works of Kang et al (1999) and Adegoke et al (2012), who reported an improvement in enzyme production in A. niger and Pluerotus pulmonarius-LAU through UV light mutation. Similarly, an improvement in cellulase production was reported by Shahbazi et al (2014) for UV mutants of Trichoderma reesei.…”
Section: Resultssupporting
confidence: 93%
“…The increased yield in mannanase production in the mutants is a proof of true strain improvement. This was in agreement with works of Kang et al (1999) and Adegoke et al (2012), who reported an improvement in enzyme production in A. niger and Pluerotus pulmonarius-LAU through UV light mutation. Similarly, an improvement in cellulase production was reported by Shahbazi et al (2014) for UV mutants of Trichoderma reesei.…”
Section: Resultssupporting
confidence: 93%
“…The supernatant was discarded, and pellet was kept at room temperature till the residual acetone evaporated. It was then dissolved in 0.1 M Tris–HCl buffer (pH 8.0) (Adegoke et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…This culture was incubated at 25 ± 2°C for 70 hours and subsequently re-introduced onto the newly prepared PDA slant, incubated for 2 weeks to obtain fully ramified UV10 strain. The wild and UV10 strains were re-evaluated for quality enhancement and used for the production of EPS using combined methods of Adebayo et al [33] and Majolagbe et al [34].…”
Section: Induction Of Physical Mutationmentioning
confidence: 99%